How Research Trends On Ethnoscience In Science Learning? A Systematic and Scoping Review Of Empirical Studies - Hasbi Iskandar; Sudarmin Sudarmin; Susilo Susilo; Mahardika Prasetyo Aji (International Conference on Science, Education, and Technology, 2022)
The science education curriculum in Indonesia is concerned with cultural characteristics local so that it can be used as a potential to develop education in several regions. increase in scientific research integrated with local culture is called ethnoscience. Thus, it's miles essential to understand the development tendencies of research on ethnoscience in activity science learning. The kind of research used in this research is a systematic literature review of ethnoscience in activity science learning. In this literature review, we analyzed 60 articles published from 2010 to 2020 and indexed on the web of science. The results of the study indicate that there are still several objects or research studies that have not been studied by researchers regarding the ethnoscience approach in activity science learning. Even though the quantity of research has increased, the amount continues to be small, with most tracking results 2020 as many as 18 articles. Most researchers on the ethnoscience approach in science learning are still dominated by researchers from Indonesia who have published in the journal of physics. In terms of the subject matter studied, the physics subject matter was the largest among chemistry and biology subjects, although the difference was not large. Data analysis using the NVivo application to know the ethnoscience research gap in science learning, it is found that there is still a chance to develop a learning model based on local culture and learning media that is integrated with other appropriate approaches.